Interventions to improve the outcomes of frail people having surgery: A systematic review. - Daniel I McIsaac; Tim Jen; Nikhile Mookerji; Abhilasha Patel; Manoj M Lalu (PLoS ONE)
Background Frailty is an important prognostic factor for adverse outcomes and increased resource use in the growing population of older surgical patients. We identified and appraised studies that tested interventions in populations of frail surgical patients to improve perioperative outcomes. Methods We systematically searched Cochrane, CINAHL, EMBASE and Medline to identify studies that tested interventions in populations of frail patients having surgery. All phases of study selection, data extraction, and risk of bias assessment were done in duplicate. Results were synthesized qualitatively per a prespecified protocol (CRD42016039909). Results We identified 2 593 titles; 11 were included for final analysis, representing 1 668 participants in orthopedic, general, cardiac, and mixed surgical populations. Only one study was multicenter and risk of bias was moderate to high in all studies. Interventions were applied pre- and postoperatively, and included exercise therapy (n = 4), multicomponent geriatric care protocols (n = 5), and blood transfusion triggers (n = 1); no specific surgical techniques were compared. Exercise therapy, applied pre-, or post-operatively, was associated with significant improvements in functional outcomes and improved quality of life. Multicomponent protocols suffered from poor compliance and difficulties in implementation. Transfusion triggers had no significant impact on mortality or other outcomes. Conclusions Despite a growing literature that demonstrates strong independent associations between frailty and adverse outcomes, few interventions have been tested to improve the outcomes of frail surgical patients, and most available studies are at substantial risk of bias. Multicenter, low risk of bias, studies of perioperative exercise are needed, while substantial efforts are required to develop and test other interventions to improve the outcomes of frail people having surgery.